The training needs of Turkish emergency department personnel regarding intimate partner violence - Aksu Feride; Aksan H Asli (BMC, 2007)
Abstract Background Violence against females is a widespread public health problem in Turkey and the lifetime prevalence of IPV ranges between 34 and 58.7%. Health care workers (HCW) sometimes have the unique opportunity and obligation to identify, treat, and educate females who are abused. The objective of this study was to evaluate the knowledge, attitudes, and experiences of the emergency department (ED) staff regarding intimate partner violence (IPV) at a large university hospital in Turkey. Methods A cross-sectional study was conducted in a large university hospital via questionnaire. The study population consisted of all the nurses and physicians who worked in the ED during a two month period (n = 215). The questionnaire response rate was 80.5% (41 nurses and 132 physicians). The main domains of the questionnaire were knowledge regarding the definition of IPV, clinical findings in victims of IPV, legal aspects of IPV, attitudes towards IPV, knowledge about the characteristics of IPV victims and abusers, and professional and personal experiences and training with respect to IPV. Results One-half of the study group were females, 76.3% were physicians, and 89.8% had no training on IPV. The majority of the nurses (89.5%) and physicians (71.1%) declared that they were aware of the clinical appearance of IPV. The mean of the knowledge scores on clinical knowledge were 8.84 ± 1.73 (range, 0-10) for acute conditions, and 4.51 ± 3.32 for chronic conditions. The mean of the knowledge score on legal procedures and the legal rights of the victims was 4.33 ± 1.66 (range, 0-7). At least one reason to justify physical violence was accepted by 69.0% of females and 84.7% of males, but more males than females tended to justify violence (chi square = 5.96; p = 0.015). However, both genders accepted that females who experienced physical violence should seek professional medical help. Conclusion The study participants' knowledge about IPV was rather low and a training program is thus necessary on this issue. Attention must be given to the legal aspects and clinical manifestations of IPV. The training program should also include a module on gender roles in order to improve the attitudes towards IPV.